SUB-ACUTE TOXICITY STUDIES OF ACETAMINOPHEN IN WISTAR RATS - P.S.VENKATESAN; M. DEECARAMAN (International Journal of Pharma and Bio Sciences, 2014)
The aim of the present study was to evaluate the sub-acute oral toxicity of acetaminophen in wistar rats at doses of 250 to 1000 mg/kg body weight. The following observations were noticed during the study. No mortality, no incidence of any abnormal clinical signs, no significant effect on body weight gain, no effect on the daily feed consumption, no toxicologically significant effect on the haematological and biochemical parameter in either sex, at and up to the dose of 1000 mg/kg body weight. No toxicologically significant effect on the urinalysis parameters, absolute and relative organ weights, gross pathological alterations and histopathological findings were observed in male and female rats treated at and up to the dose of 1000 mg/kg body weight. Based on the findings of this study, the No Observed Adverse Effect Level (NOAEL) of acetaminophen in Wistar rats, following oral administration at the doses of 250, 500 and 1000 mg/kg on daily basis was found to be 1000 mg/kg body weight.